Deteksi dan Identifikasi Dickeya sp. sebagai Organisme Pengganggu Tumbuhan Karantina A2 pada Tanaman Kentang di Jawa - Haerani Haerani; Abdjad Asih Nawangsih; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2015)
Erwinia chrysanthemi (currently Dickeya sp.) is one of the A2 quarantine pest that must be concerned of its distribution on potato in Indonesia. The aim of this study is to detect and identify E. chrysanthemi from potato in Java. A total of 400 samples of potato plants showing symptoms of soft rot were obtained from several potato areas in Pangalengan and Garut (West Java), Dieng (Central Java), and Batu-Malang (East Java). Disease incidence was determined by indirect enzyme-linked immunosorbent assay (I-ELISA) using polyclonal antiserum. E.chrysanthemi was isolated from plant samples with positive ELISA results. Furthermore, bacterial isolates were characterized by GEN III OmniLog ID System and PCR using specific primers Ec3F/Ec4R, as well as the universal 16S rRNA primer pair of 27F/1429R. The incidence of E. chrysanthemi based on ELISA was obtained. Based on physiological characters; Gram, catalase, oxidase, and oxidation-fermentation, there were 4 isolates similar to the genus of Erwinia. However, the results of Gen III OmniLog System, PCR, and nucleotide sequences analysis of 16S rRNA confirmed that none of the isolates were identified as E.chrysanthemi. Otherwise, those 4 isolates were identified as Pseudomonas oryzihabitans, Pantoea agglomerans, and Pseudomonas viridiflava. The result of this study indicated that the existence of E. chrysanthemi as an A2 quarantine pest on potato in Java can not be confirmed and remains as an A1 quarantine pest.